Nanohole structure as efficient antireflection layer for silicon solar cell fabricated by maskless laser annealing - Hong, Lei (2013)
In this paper, a uniform nanohole structure on silicon wafer is fabricated using the silver catalyst induced method. The optical properties of the silicon nanohole structure are studied systematically at different nanohole depths. The nanohole arrays demonstrate excellent antireflection property due to its sub-wavelength structure with a low reflection loss of 4% for incident light within the wavelength range of 300-1100 nm. The angular dependence of reflectivity is also investigated. The average reflection decreases at first and then increases as the incident light deviated from normal, with a very lower reflectivity of 0.83% at an incident angle of 20°. The suppressed reflection indicates a strong light trapping ability of the nanohole structure, and provides a low cost method to enhance light absorption and performance for the solar cell application.